Functional crosstalk between the mitochondrial PTP and KATP channels determine arrhythmic vulnerability to oxidative stress - Xie, Chaoqin; Kauffman, Justin; Akar, Fadi G. (Frontiers in Physiology, 2014)
Background: Mitochondrial permeability transition pore (mPTP) opening is a terminal event leading to mitochondrial dysfunction and cell death under conditions of oxidative stress (OS). However, mPTP blockade with cyclosporine A (CsA) has shown variable efficacy in limiting post-ischemic dysfunction and arrhythmias. We hypothesized that strong feedback between energy dissipating (mPTP) and cardioprotective (mKATP) channels determine vulnerability to OS. Methods and Results: Guinea pig hearts (N = 61) were challenged with H2O2 (200 μM) to elicit mitochondrial membrane potential (ΔΨm) depolarization. High-resolution optical mapping was used to measure ΔΨm or action potentials (AP) across the intact heart. Hearts were treated with CsA (0.1 μM) under conditions that altered the activity of mKATP channels either directly or indirectly via its regulation by protein kinase C. mPTP blockade with CsA markedly blunted (P < 0.01) OS-induced ΔΨm depolarization and delayed loss of LV pressure (LVP), but did not affect arrhythmia propensity. Surprisingly, prevention of mKATP activation with the chemical phosphatase BDM reversed the protective effect of CsA, paradoxically exacerbating OS-induced ΔΨm depolarization and accelerating arrhythmia onset in CsA treated compared to untreated hearts (P < 0.05). To elucidate the putative molecular mechanisms, mPTP inhibition by CsA was tested during conditions of selective PKC inhibition or direct mKATP channel activation or blockade. Similar to BDM, the specific PKC inhibitor, CHE (10 μM) did not alter OS-induced ΔΨm depolarization directly. However, it completely abrogated CsA-mediated protection against OS. Direct pharmacological blockade of mKATP, a mitochondrial target of PKC signaling, equally abolished the protective effect of CsA on ΔΨm depolarization, whereas channel activation with 30 μM Diazoxide protected against ΔΨm depolarization (P < 0.0001). Conditions that prevented mKATP activation either directly or indirectly via PKC inhibition led to accelerated ΔΨm depolarization and early onset of VF in response to OS. Investigation of the electrophysiological substrate revealed accelerated APD shortening in response to OS in arrhythmia-prone hearts. Conclusions: Cardioprotection by CsA requires mKATP channel activation through a PKC-dependent pathway. Increasing mKATP activity during CsA administration is required for limiting OS-induced electrical dysfunction.